Christian and secular values for sale: the religious apostasy of celebrity and Disney's "Hannah Montana" star Miley Cyrus - Sanchez Sabate; Gelabert Santané; Badilla Briones; Del Valle Rojas (Acta Theologica)
Religious apostasy is a complex phenomenon that becomes even more obscure when it involves public figures in the media industry with economic interests at stake. A paradigmatic case is that of American singer Miley Cyrus, who went from being a famous religious role model for conservative American evangelical Christians to becoming a secular and liberal celebrity, playing in highly sexualized live shows and videos. Drawing on a complementary use of sociological, economic and language theories of value, this paper explores Cyrus’ religious apostasy as a transformation from a Christian commodity to a secular one. Our study shows that, while for the industry, be it Christian or secular, Cyrus’ sociological and language values are always subsidiary to her economic value as a commodity, for Christian consumers, her economic value depends on her social and language values.